2020
DOI: 10.1016/j.nima.2020.164076
|View full text |Cite
|
Sign up to set email alerts
|

Betatron radiation diagnostics for AWAKE Run 2

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The correlation between betatron radiation and the electron dynamics has shown that we might be able to use betatron radiation to indirectly measure the evolution of the beam size or even beam profile inside the plasma tube. However, as also shown by this work and the previous study [16], there are several difficulties in the study and the application of betatron diagnostics for proton wakefield acceleration experiments. The main problem from the physical side is the acceleration-leaded witness beam evolution, which then changes the characteristics of the betatron radiation emitted at each moment along the acceleration path.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The correlation between betatron radiation and the electron dynamics has shown that we might be able to use betatron radiation to indirectly measure the evolution of the beam size or even beam profile inside the plasma tube. However, as also shown by this work and the previous study [16], there are several difficulties in the study and the application of betatron diagnostics for proton wakefield acceleration experiments. The main problem from the physical side is the acceleration-leaded witness beam evolution, which then changes the characteristics of the betatron radiation emitted at each moment along the acceleration path.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the divergence term Θ(θ d ) can be retrieved from the correlation between θ d and r β . However, as aforementioned, the evolution of the electron beam energy and its transverse profile during the acceleration may prohibit us to reconstruct the beam profile with this simple analytical model if the measured radiation is integrated over multiple betatron periods as in the case of AWAKE [16]. A spectrometer that can resolve the single period emission (sub-fs) or a model that considers the electron beam evolution is required.…”
Section: Betatron Radiation In Plasma Ion Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between BR and the electron dynamics has shown that we may possibly use BR to indirectly get information about the evolution of the electron beam. However, as shown by this work and the previous study (Williamson et al 2020), there are several difficulties in the application of betatron diagnostics for the AWAKE. FIGURE 7.…”
Section: Discussionmentioning
confidence: 64%
“…The betatron radiation signal is accessible due to the large radiation flux generated by relativistic beams in plasmas. Betatron radiation diagnostics have been utilized in inverse Compton scattering experiments [15], and studied in proton-driven PWFA experiments at AWAKE [16,17]. While the implementation of betatron radiation diagnostics was attempted at FACET, the high emittance of the beams prevented it from meeting its full potential.…”
Section: Introductionmentioning
confidence: 99%